Rumen Fluid from Slaughtered Animals: A Standardized Procedure for Sampling, Storage and Use in Digestibility Trials - Riccardo Fortina; Sara Glorio Patrucco; Salvatore Barbera; Sonia Tassone (Methods and Protocols, 2022)
Digestibility trials need a viable rumen fluid as inoculum to degrade feeds. The variability of rumen fluid depends on the animal’s diet, while its viability is greatly influenced by the sampling and handling procedures. In this article, we present a replicable protocol for sampling the rumen fluid from slaughtered animals for in vitro digestibility trials. A detailed list of the tools and a step-by-step standardized procedure for the collection, storage and the transportation of the rumen fluid from the slaughterhouse to the laboratory is presented. We also describe a digestibility trial for establishing the maximum storage time of rumen fluid from sampling to its use. The results show that the rumen fluid, collected and maintained according to the proposed protocol, can be stored and used from 30 to 300 min from sampling without significantly compromising the fermentative activity of the microbial population.